A method for learning scenario determination and modification in intelligent tutoring systems - Kozierkiewicz-Hetmańska, Adrianna; Nguyen, Ngoc Thanh (Zielona Góra: Uniwersytet Zielonogórski)
Computers have been employed in education for years. They help to provide educational aids using multimedia forms such as films, pictures, interactive tasks in the learning process, automated testing, etc. In this paper, a concept of an intelligent e-learning system will be proposed. The main purpose of this system is to teach effectively by providing an optimal learning path in each step of the educational process. The determination of a suitable learning path depends on the student?s preferences, learning styles, personal features, interests and knowledge state.
Keywords: e-learning system; intelligent tutoring system; learning scenario; personalization